Exposure to atmospheric particulate matter enhances Th17 polarization through the aryl hydrocarbon receptor. - Michael van Voorhis (Public Library of Science (PLoS), 2013)
Lung diseases, including asthma, COPD, and other autoimmune lung pathologies are aggravated by exposure to particulate matter (PM) found in air pollution. IL-17 has been shown to exacerbate airway disease in animal models. As PM is known to contain aryl hydrocarbon receptor (AHR) ligands and the AHR has recently been shown to play a role in differentiation of Th17 T cells, the aim of this study was to determine whether exposure to PM could impact Th17 polarization in an AHR-dependent manner. This study used both cell culture techniques and in vivo exposure in mice to examine the response of T cells to PM. Initially experiments were conducted with urban dust particles from a standard reference material, and ultimately repeated with freshly collected samples of diesel exhaust and cigarette smoke. The readout for the assays was increased T cell differentiation as indicated by increased generation of IL-17A in culture, and increased populations of IL-17 producing cells by intracellular flow cytometry. The data illustrate that Th17 polarization was significantly enhanced by addition of urban dust in a dose dependent fashion in cultures of wild-type but not AHR(-/-) mice. The data further suggest that polycyclic aromatic hydrocarbons played a primary role in this enhancement. There was both an increase of Th17 cell differentiation, and also an increase in the amount of IL-17 secreted by the cells. In summary, this paper identifies a novel mechanism whereby PM can directly act on the AHR in T cells, leading to enhanced Th17 differentiation. Further understanding of the molecular mechanisms responsible for pathologic Th17 differentiation and autoimmunity seen after exposure to pollution will allow direct targeting of proteins involved in AHR activation and function for treatment of PM exposures.